2017
DOI: 10.1007/s00442-017-4014-1
|View full text |Cite
|
Sign up to set email alerts
|

Stabilising selection on immune response in male black grouse Lyrurus tetrix

Abstract: Illnesses caused by a variety of micro- and macro- organisms can negatively affect individuals’ fitness, leading to the expectation that immunity is under positive selection. However, immune responses are costly and individuals must trade-off their immune response with other fitness components (e.g. survival or reproductive success) meaning that individuals with intermediate response may have the greatest overall fitness. Such a process might be particularly acute in species with strong sexual selection becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
3
1
Order By: Relevance
“…However, our findings do not align with most empirical studies that report positive directional selection on immune activity (reviewed by Seppälä 2015). In addition to L. stagnalis (Langeloh et al 2017, this study), stabilizing selection on quantitative immune defence traits has been reported in three bird species, blue tit (antibody responsiveness to diphtheria; Råberg and Stjernman 2003), common kestrel (PHA test; Kim et al 2013) and black grouse (antibody responsiveness to tetanus; Soulsbury et al 2018). Furthermore, negative directional selection on antibody responsiveness to tetanus has been detected in specific populations of the common side-blotched lizard that live under low infection risk (i.e.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…However, our findings do not align with most empirical studies that report positive directional selection on immune activity (reviewed by Seppälä 2015). In addition to L. stagnalis (Langeloh et al 2017, this study), stabilizing selection on quantitative immune defence traits has been reported in three bird species, blue tit (antibody responsiveness to diphtheria; Råberg and Stjernman 2003), common kestrel (PHA test; Kim et al 2013) and black grouse (antibody responsiveness to tetanus; Soulsbury et al 2018). Furthermore, negative directional selection on antibody responsiveness to tetanus has been detected in specific populations of the common side-blotched lizard that live under low infection risk (i.e.…”
Section: Discussioncontrasting
confidence: 90%
“…the highest trait values lead to the highest fitness; reviewed by Seppälä 2015). Only a few empirical studies show stabilizing selection on such immune parameters (Råberg and Stjernman 2003, Kim et al 2013, Langeloh et al 2017, Soulsbury et al 2018). This discrepancy between theoretical predictions and empirical observations, and the variation in the form of observed selection in empirical studies, highlight the need for examining underlying factors that influence the form and strength of natural selection on immune function.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of empirical selection gradients on the mean in natural populations have shown weak directional selection to be common (Blows & Brooks, 2003;Kingsolver, Diamond, Siepielski, & Carlson, 2012;Kingsolver et al, 2001). But many traits with a close connection to fitness are under strong stabilizing selection on the mean (for recent examples, see González Marín, Olave, Avila, Sites, & Morando, 2018;Sanjak, Sidorenko, Robinson, Thornton, & Visscher, 2018;Soulsbury, Siitari, & Lebigre, 2018). When stabilizing selection on the mean is strong and the trait mean approaches the optimum, genotypes increasing V e will be at a disadvantage as they are likely to produce a nonoptimal phenotype (Bull, 1987;Gavrilets & Hastings, 1994;Slatkin & Lande, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…We did, however, find mixed and significant associations of tick burdens with lymphocyte and basophil counts, H:L ratios, and body condition indices. These associations varied by sex, size, and hemoparasite infection rate supporting the supposition that different life stages of animals may invest differently in immune responses (Jackson et al, ; Soulsbury, Siitari, & Lebigre, ), or impacts may be modulated based on size and sex of hosts.…”
Section: Discussionmentioning
confidence: 66%